Ab initio and Time Dependent Density Functional Theory Study of the Structural and Spectral Properties of Two Flavones Derived from Limnophila indica Species - Dutta, P.; Dutta, M. (Asian Journal of Chemistry, 2011)
Flavonoids constitute a large group of polyphenolic phytochemicals widely distributed in nature. The overwhelming capability of such species to act as an antioxidant by direct free radical scavenging and their capacity of metal chelation have made their properties a subject of continuous research. Herein, we wish to report a theoretical study, both in gas phase and in chloroform medium, carried out on two flavonoids namely 5-hydroxy-7,2'-dimethoxy flavone and 5,2'-dihydroxy-7,8-dimethoxy flavone derived from Limnophila indica species. Time dependent density functional theory calculations using the Gaussian 03 suite of programmes gives an excellent opportunity to predict structural and spectroscopic properties of such flavone species. Optimization of the flavonoids by HF, B3LYP, mPW1PW91 methods at 6-31++G(d,p) and 6-311+G(2d,p) levels confirmed their twisted structure. The UV-VIS spectra of both the flavones were calculated by time dependant density function theory under the polarizable continuum model and the results are in good agreement with the experimentally observed value. The theoretically calculated infrared absorption bands, 1H and 13C NMR spectra of these flavones agree well with the reported experimental data.